University Faculty Perceptions of Their Instructional Strategy - Duong, Minh-Quang (ASEAN Journal of Education, 2023)
This study explored the faculty members’ perception of their instructional strategy at the University of Social Sciences and Humanities – Vietnam National Universi t y of Ho Chi Minh City (USSH-VNUHCM) and the relationship that teaching resources, organizational culture and administrative support factors affect faculty instructional strategy were examined. A survey questionnaire measuring four factors of instructional strategy was distributed to 124 faculty members working full-time at the USSH-VNUHCM. The results indicate that most faculty members measured strongly towards their instructional strategy. In addition, the results also indicate that the different regression models had different explanation for faculty instruct i onal strategy across different factors. Generally, factors of teaching resources, organizational culture and administrative support yielded significantly differen c e that affect faculty members’ instructional strategy. The study’s implications for university management are discussed.